Struktur Komunitas Hymenoptera Parasitoid Pada Ekosistem Sayuran dan Vegetasi Non-Crop di Sumatera Barat - Yaherwandi, Yaherwandi (Universitas Syiah Kuala, 2010)
Hymenoptera parasitoids have an important role in agroecosystem because of their ability in suppressing pest population. Their presences in the field are seen as the key to agricultural ecosystem. Their presence can be influenced by the availability of non-crop vegetation. Some adult Hymenoptera parasitoids require food in the form of pollen and nectar of wild flowers to ensure effective reproduction and longevity. The objective of this research is to study Hymenoptera parasitoid communities in vegetable field and non-crop vegetation at Alahan Panjang and Kayu tanduak agricultural landscapes. Insects were sampled by two trapping techniques (farmcop and sweep net) in one lines of transect for each landscape. Total of 62species from 19 families of Hymenoptera parasitoid were collected invegetable field and non-crop vegetation at Alahan Panjang and Kayu Tanduak landscape. Landscape structure affected the species richness, diversity and evenness of Hymenoptera parasitoid invegetable field and non-crop vegetation.